The flower of friendship : a Renaissance dialogue contesting marriage - Tilney, Edmund, -1610 (Cornell University Press, 1992)
Edmund Tilney dedicated to Queen Elizabeth in I568-a time when she was under considerable pressure to marry-a spirited dialogue concerning appropriate behavior in marriage. In Tilney's conduct book, which was modeled on Erasmus's Conjugium and Castiglione's Courtier, fictional counterparts to such notables as Vives, Erasmus, Heloise, and the queen herself all make an appearance to offer advice on how to nurture the flower of friendship within marriage. Extraordinarily popular for a generation following its first publication, it is available here for the first time in a critical edition that includes a comprehensive essay by Valerie Wayne. In her introduction, Wayne examines the dialogue's competing notions of conjugality within their historical and literary contexts and illustrates the impact of humanism on Protestant and Puritan positions. Since marriage was the most common means by which Renaissance women in Protestant countries could sustain themselves outside their parental home, ideologies of marriage became a primary means by which women were constructed as subjects. Wayne explores the range of ideologies presented in The Flower of Friendship, illuminating the contradictory claims of the humanist position in relation to the conflicts within Elizabethan culture over the queen's resistance to marriage. This edition of a lively debate on marital and sexual conduct in the Renaissance will be welcomed by students and scholars of Renaissance literature, culture, and history, and by others interested in gender issues and the history of marriage.